Human Histone Interaction Networks: An Old Concept, New Trends. Issue 6 (19th March 2021) - Peng, Yunhui; Markov, Yaroslav; Goncearenco, Alexander; Landsman, David; Panchenko, Anna R.
Graphical abstract: Highlights: Constructed human histone interaction networks by using structural, chemical cross-linking and high-throughput studies. Histone interactomes derived from different data sources have limited overlap and complement each other. Human histone interactome is scale free and shows high modularity. Histones of different types have distinctive binding interfaces and binding hot spots. Abstract: To elucidate the properties of human histone interactions on the large scale, we perform a comprehensive mapping of human histone interaction networks by using data from structural, chemical cross-linking and various high-throughput studies. Histone interactomes derived from different data sources show limited overlap and complement each other. It inspires us to integrate these data into the combined histone global interaction network which includes 5308 proteins and 10, 330 interactions. The analysis of topological properties of the human histone interactome reveals its scale free behavior and high modularity. Our study of histone binding interfaces uncovers a remarkably high number of residues involved in interactions between histones and non-histone proteins, 80–90% of residues in histones H3 and H4 have at least one binding partner. Two types of histone binding modes are detected: interfaces conserved in most histone variants and variant specific interfaces. Finally, different types of chromatin factors recognize histones in nucleosomes via distinct binding modes, and many of these interfaces utilize acidic patches among other sites. Interaction networks are available at https://github.com/Panchenko-Lab/Human-histone-interactome .